Simultaneous treatment with palm-LEAP2(1-14) and feeding high-fat diet attenuates liver lipid metabolism but not obesity: Sign of selective resistance to palm-LEAP2(1-14) - Peteláková, Martina; Neprašová, Barbora; Šmotková, Zuzana; Myšková, Aneta; Holá, Lucie; Petelák, Aleš; Áčová, Andrea; Cantel, Sonia; Fehrentz, Jean-Alain; Sýkora, David; Kuneš, Jaroslav; Železná, Blanka; et al. (Molecular and cellular endocrinology, 2025)
Liver-enriched antimicrobial peptide 2 (LEAP2) is a natural antagonist/inverse agonist of ghrelin receptor GHSR. Its truncated palmitoylated analog palm-LEAP2(1-14) promised anti-obesity properties because it exhibited favourable stability and an acute anorexigenic effect in our previous studies. Here we demonstrate desirable palm-LEAP2(1-14) pharmacokinetics, with significant levels of the peptide persisting in mouse blood 3 h after its subcutaneous administration. Palm-LEAP2 (1-14) reduced ghrelin-induced c-Fos immunoreactivity in arcuate nucleus and area postrema, in line with previously described silencing of ghrelin orexigenic effect. In spite of this, anti-obesity effect was not reached by two-week palm-LEAP2(1-14) treatment in mice with diet-induced obesity. Similarly, palm-LEAP2(1-14) administered simultaneously with high-fat diet feeding for 8 weeks did not protect mice from development of obesity and related biochemical changes. However, palm-LEAP2(1-14) kept its ability to attenuate liver de novo lipogenesis, and prominently lowered liver gene expression of nuclear receptors PPARG, SREBF1 and PPARA, and also expression of lipogenic and lipolytic enzymes. In our recent study, we described a high-fat diet-induced ghrelin resistance, reversible by switch to standard diet, followed by resistance to the acute anorexigenic effects of palm-LEAP2(1-14). Here we conclude that this resistance to palm-LEAP2(1-14) in obesity is probably selective and does not concern its ability to inhibit liver lipid metabolism.
Keywords: Liver; Animals; ghrelin; lipogeneze; játra; Diet, High-Fat; Obesity; kationické antimikrobiální peptidy; Lipid Metabolism; Mice; myši; metabolismus lipidů; peptidové fragmenty; Receptors, Ghrelin; Blood Proteins; LEAP2; krevní proteiny; Diet-induced obesity; obezita; Male; Peptide Fragments; Lipid metabolism; Palm-LEAP2(1–14); Ghrelin; Lipogenesis; Antimicrobial Cationic Peptides; mužské pohlaví; zvířata; Mice, Inbred C57BL; dieta s vysokým obsahem tuků; LEAP2 resistance; receptory ghrelinu; myši inbrední C57BL